Fruit Volatile Fingerprints Characterized among Four Commercial Cultivars of Thai Durian (Durio zibethinus) - Wattana Aschariyaphotha; Chalermchai Wongs-Aree; Kitti Bodhipadma; Sompoch Noichinda (Journal of Food Quality)
Ripe durian fruits produce unique volatiles of pungent odor comprising esters, alcohols, ketones, and sulfur-containing compounds. Recently, “Chanthaburi 1” hybrid bred from 2 famous commercial cultivars of “Chanee” and “Monthong” claimed to be less fragrant during ripening, but there was no report. The present study compared the volatile profiles from 3 Thai commercial cultivars of “Kanyao,” “Chanee,” and “Monthong” compared to “Chanthaburi 1”, and the relationships of the cultivars were organized using the volatile fingerprints. Out of 41 volatile compounds detected by SPME/GC-MS in ripe durian flesh, 33 compounds were esters, but only 14 esters were found in “Chanthaburi 1.” Ripe flesh of most durian cultivars contains ethyl-2-methyl butanoate and ethyl hexanoate as the active volatiles. “Chanthaburi 1” contained fewer components with low odor activity value (OAV) of the volatiles. “Chanee” ripe flesh exhibited the strongest durian smell among the four varieties, whereas “Monthong” exhibited a strong apple-like fruity odor and “Kanyao” was more green fruity. Diethyl disulfide and 3, 5 dimethyl-1, 2, 4-trithiolane contributing pungent smells of garlic or onion were found only in “Chanthaburi 1” and “Monthong.” In terms of detected volatiles, “Kanyao” and “Chanee” were highly close when “Monthong” was apart. PCA analysis revealed that “Chanthaburi 1” contained ester compounds ancestrally related to the parents, “Chanee” in the component I and “Monthong” in the component II. These data could be beneficial for managing the status of Thai durians in global markets.